The Impact of Service Quality, Pricing Strategies, User Trust, and Technological Innovation in Indonesia's Online Transportation Services Industry - Taufiur Rahman, Rahmat; Bahar, Anisa; Prananta, Arie Wahyu; Afifudin, Moch (International Journal of Business, Law, and Education, 2024)
This study investigates the impact of service quality, pricing strategies, user trust, and technological innovation on customer satisfaction in Indonesia's online transportation services industry. Using a sample of 400 respondents, the research employs regression analysis to identify the relationships between these variables. The findings reveal that service quality is the most significant predictor of customer satisfaction, followed by user trust, pricing strategies, and technological innovation. The results highlight the interrelated nature of these factors, suggesting that improvements in one area can positively influence the others. The study underscores the importance of maintaining high service standards, establishing user trust, implementing effective pricing strategies, and leveraging technological advancements to enhance customer satisfaction. These insights provide valuable implications for practitioners aiming to optimize user experiences and foster loyalty in a competitive market.